Business Planning Training Using Business Model Canvas for Student Community in West Jakarta - Rahmatika, Rizka Astari; Elania, Secuandra; Larasati, Hasna (SEEIJ (Social Economics and Ecology International Journal), 2022)
The training was conducted on July 12, 2022, as a part of a community development program with a community of university students, namely AyoKreasi Community. The problem faced by this community is the lack of business planning knowledge, which frequently becomes a factor which causes individuals’ hesitancy in starting or carrying out a business. Therefore, the students in the community need to understand some tools which could be used in the business planning phase. One of the tools in business planning is the Business Model Canvas (BMC). The training was conducted online, considering the Covid-19 Pandemic. In the training session, the presenter delivered the material through seminar, case study, discussions, as well as questions and answers sessions. At the end of the training, a post-test quiz was conducted as a part of an evaluation process to measure the participants’ learning process after the seminar was delivered. The quiz result showed that 85% of the participants were actively engaged, and most of them acquired a good level of understanding regarding the Business Model Canvas after the training was delivered.